Integrating Psychologists into the Canadian Health Care System: The Example of Australia - Moulding, Richard (Can J Public Health, 2009)
Canada and Australia share many similarities in terms of demographics and the structure of their health systems; however, there has been a divergence in policy approaches to public funding of psychological care. Recent policy reforms in Australia have substantially increased community access to psychologists for evidence-based treatment for high prevalence disorders. In Canada, access remains limited with the vast majority of consultations occurring in the private sector, which is beyond the reach of many individuals due to cost considerations. With the recent launch of the Mental Health Commission of Canada, it is timely to reflect on the context of the current Canadian and Australian systems of psychological care. We argue that integrating psychologists into the publicly-funded primary care system in Canada would be feasible, beneficial for consumers, and cost-effective.